Politik Hijrah Kartosuwiryo; Menuju Negara Islam Indonesia - Riyadi Suryana (Universitas Nahdlatul Ulama Surabaya, 2019)
This research explores about the Politics of Hijrah by Sekarmadji Maridjan Kartosuwiryo. Been inheriting the narrative expertise from the figure of the awakening of Islam in Indonesia as well as the founder of PSII (Syarikat Islam Indonesia Party), HOS Cokroaminoto, Kartosuwiryo existed to continue the struggle of Islam in Indonesia through the Politics of Hijrah concept. The main problems in this research are the beginning, the conceptual framework, and the function of the Politics of Hijrah which was initiated by S.M. Kartosuwiryo. Therefore, the limitation of this study is the problematics of the Politics of Hijrah in the period between 1931 and 1962. Written in political science approach, this research aims to explores the details of the circumstances in Indonesia before the independence, the history and struggle of Kartosuwiryo, and the justification of the Politics of Hijrah itself. This research found that there were several groups or organisation founded political parties competed the ideology of nationalist and Islamist, thus this condition has differentiated the direction of the movement shown by each of the political parties. According to this, some of the parties have made coordination with the Dutch Indies government, while some others have chosen the non-coordinative way. Kartosuwiryo has chosen the later through the idea of the Politics of Hijrah and proclaimed the establishment of Islamic State of Indonesia.